DEMOCRATIC SCHOOL MANAGEMENT: ITS IMPORTANCE IN THE EDUCATIONAL PROCESS - Bartinelly Sousa da Silva Melo, Sílvia (Revista Gênero e Interdisciplinaridade, 2023)
The educational environment, as a significant social provider, is the result of a collection of protagonists, who, in turn, as demanders of education, have responsibilities that are often not properly assumed. The present article brings to the question the democratization of school management. It presents the high level of difficulty that this action brings with it, considering the experience in a society whose standards are filled with authoritarianism, based on an exacerbated exercise of power not only in a political vision, but also social and economic. The little one reproduces itself and thereby produces the great; and the school, as an institution of the system, is subject to this ambiguous, or perhaps even contradictory, relation as it incorporates the very title of the article. There is a whole historical movement in the search of decentralizing the power in the management of public policies that attempt in the direction of the municipal power. However, a question runs through what is said in this article: how to democratize school in a society that, at times, still resists the basic principles of democracy? This work does not have definite and conclusive answers, but it is concerned with pointing out certain biases that may (or may not) lead to a democratized school process, from a management that makes democracy its greatest desire. In accordance with the information acquired during the work, at the end some considerations are established, through which it is intended to assist other research that may be triggered.